Views and Attitudes of Secondary Education Teachers for the Education of Students with Disabilities, Using Technology - Λεοντίου Χριστίνα; Δαμιανίδου Ελένη (Education Sciences, 2023)
This article discusses the views and attitudes of secondary education teacher regarding the use of technology for the education of disable children. In order to answer the research questions, a survey was conducted. The main research tool was the structured questionnaire. In total 157 secondary education teachers from randomly selected schools of Nicosia participated in the research. Based on data analysis, the participants indicated a positive attitude towards the use of technology for the education of disabled children. In addition, the participants postulated that they use technology in their classroom for the education of disabled children in many ways, mainly the computer and electronic games. When they were asked whether they used technology for particular disabilities, their answers indicated a low or no use. The main barriers in using technology, were inadequate training and lack of infrastructure. Finally, it was found that frequency of use may be increased, if the teachers’ attitude towards the use of technology improves.